2022
DOI: 10.3389/fmicb.2022.998505
|View full text |Cite
|
Sign up to set email alerts
|

Screening of interferon-stimulated genes against avian reovirus infection and mechanistic exploration of the antiviral activity of IFIT5

Abstract: Screening of interferon-stimulated genes against avian reovirus infection and mechanistic exploration of the antiviral activity of IFIT5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Understanding the related functions of IFI27L1 is of guiding significance for the study of IFI6. A few literatures have shown that IFI27L1 is a protein that can promote apoptosis (Xie et al, 2022). This provides clues for future research on the function of avian IFI6.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Understanding the related functions of IFI27L1 is of guiding significance for the study of IFI6. A few literatures have shown that IFI27L1 is a protein that can promote apoptosis (Xie et al, 2022). This provides clues for future research on the function of avian IFI6.…”
Section: Discussionmentioning
confidence: 80%
“…Studies have found that ARV infection activates the expression of many innate immune response-related factors in a host. ARV S1133 infection in specific-pathogen-free chickens can induce changes in the expression of various innate immunity-related factors, including IFN-α, IFN-β, IFN-γ, IL-6, IL-17, IL-18, MX, IFITM3, PKR, OAS, IFIT5, ISG12, VIPERIN, and IFI6, in chicken peripheral blood lymphocytes and joints ( Xie et al, 2019 ; Wang et al, 2021 , 2022 ). In addition, many studies have aimed to understand the intracellular molecular mechanisms underlying the effects of ARV infection.…”
Section: Introductionmentioning
confidence: 99%
“…IFIT5 inhibits the replication of many viruses in the host through the type I IFN signaling pathway. For example, it plays a key role in inhibiting the replication of the highly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV) that infects porcine pulmonary microvascular endothelial cells [38,39]. HAX-1 is an apoptosis inhibitor that is primarily located in the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the expression of ARV σC gene and innate immune signaling pathway-correlated molecules were detected by real-time fluorescence quantitative PCR (RT–qPCR). The utilized primers [ 12 , 14 , 28 ] were described previously ( Table 1 ). In addition, the abovementioned culture medium was diluted for the infection of DF-1 cells.…”
Section: Methodsmentioning
confidence: 99%
“…IFN induces the production of many interferon-stimulated genes (ISGs) by activating the JAK/STAT signaling pathway [ 10 ], and ISGs are the main executors of IFN antiviral functions [ 11 ]. Studies have shown that ARV infection can induce the transcriptional expression of IFN-α, IFN-β and ISGs such as IFITM1, IFITM3, IFIT5, Mx, ISG12 and other cytokines in various tissues and organs; at the early stage of ARV infection, IFITM3 is significantly upregulated in peripheral blood lymphocytes, joints, the thymus and the bursa of Fabricius and shows a consistent trend with the viral load of ARV in these tissues and organs, which suggests that IFITM3 plays a crucial role in ARV infection [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%